2009
DOI: 10.1107/s1744309109002218
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution structure of proteinase K cocrystallized with digalacturonic acid

Abstract: PDB Reference: proteinase K-digalacturonic acid complex, 3dyb, r3dybsf.Proteinase K, a subtilisin-like fungal protease, was crystallized from a cocktail of small molecules containing digalacturonic acid (DGA). The crystal structure was determined to 1.32 Å resolution and refined to an R factor of 0.158. The final model contained, beside the protein, two calcium ions, 379 water molecules, a molecule of DGA and a partially occupied HEPES molecule. The DGA molecule has one sugar moiety disposed exactly on a cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Two synthetic cases were chosen with different sizes and symmetries. Proteinase K (PK) is a 30 kDa monomer with no symmetry [ 22 ], while lumazine synthase (LS) is a 1.03 MDa 60-mer with icosahedral symmetry [ 23 ]. Density maps of these were calculated from the crystal structures, randomly projected, gaussian noise added to the projections ( Figure 1a ), and the resultant images aligned to the density maps using all information up to Nyquist frequency (2 Å in these cases).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two synthetic cases were chosen with different sizes and symmetries. Proteinase K (PK) is a 30 kDa monomer with no symmetry [ 22 ], while lumazine synthase (LS) is a 1.03 MDa 60-mer with icosahedral symmetry [ 23 ]. Density maps of these were calculated from the crystal structures, randomly projected, gaussian noise added to the projections ( Figure 1a ), and the resultant images aligned to the density maps using all information up to Nyquist frequency (2 Å in these cases).…”
Section: Resultsmentioning
confidence: 99%
“…Two structures were selected, the first is the asymmetric proteinase K (PK) ( http://www.rcsb.org , PDB-3DYB [ 22 ]), and the second is the icosahedral lumazine synthase (LS) ( http://www.rcsb.org , PDB-1NQX [ 23 ]). Both were converted to 3D density maps using the program bsf [ 9 ] with a pixel size of 1 Å and sizes of 80 3 and 200 3 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…McPherson and co-workers have demonstrated that proteins can and will select specific small molecules from a multicomponent solution and that often these compounds can be structurally resolved Larson, Day, Nguyen et al, 2010;Larson et al, 2009aLarson et al, ,b, 2008Larson et al, , 2007b.…”
Section: Discussionmentioning
confidence: 99%
“…P06873). PROK is a study model of serine proteases (Larson et al, 2009). The materials and methods used to obtain PROK crystals, including the soaking and harvesting procedures, are described in Section S1.…”
Section: Figurementioning
confidence: 99%